2019
DOI: 10.2739/kurumemedj.ms661008
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Bilateral Anterior Shoulder Dislocation Following Epileptic Seizure: A Case Report and Literature Review

Abstract: Anterior shoulder dislocations following an epileptic event are considered rare. An extremely rare case of a 41 year old female suffering from bilateral anterior shoulder dislocation with concomitant greater tuberosities fractures after an epileptic seizure is presented. The patient presented to the outpatient orthopaedic clinic due to persistent pain and restriction of shoulders movement, 4 weeks after an epileptic seizure. Clinical examination and radiological evaluation established the diagnosis of bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…MRI is also recommended in most cases to evaluate for other pathologies such as anterior or inferior glenoid labrum tears (Bankart lesions), humeral head injuries (Hill-Sachs lesions), rotator cuff tears, etc. Definitive treatment can range from simple nonoperative management in a sling followed by physical therapy, to shoulder arthroscopy and labral repair or rotator cuff repair, to arthroscopic or open stabilization using bone grafting or Latarjet [2,6,15,[17][18][19][20]. Complications of dislocation and surgical intervention can include neurologic injury, shoulder stiffness or loss of motion, avascular necrosis [15,18], degenerative joint disease, and recurrent instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is also recommended in most cases to evaluate for other pathologies such as anterior or inferior glenoid labrum tears (Bankart lesions), humeral head injuries (Hill-Sachs lesions), rotator cuff tears, etc. Definitive treatment can range from simple nonoperative management in a sling followed by physical therapy, to shoulder arthroscopy and labral repair or rotator cuff repair, to arthroscopic or open stabilization using bone grafting or Latarjet [2,6,15,[17][18][19][20]. Complications of dislocation and surgical intervention can include neurologic injury, shoulder stiffness or loss of motion, avascular necrosis [15,18], degenerative joint disease, and recurrent instability.…”
Section: Discussionmentioning
confidence: 99%
“…In both of our cases, a his-tory, physical exam, and imaging were important factors in making a diagnosis, and treatment generally consisted of antiepileptic medications and orthopedic consultation. Orthopedic intervention may vary widely because of the heterogeneous nature of the injuries, but treatment may be operative or nonoperative and may include internal fixation or a multitude of strategies aimed at restoring stability to an unstable joint [2,6,15,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…O'Connor-Read et al [ 15 ] postulated that anterior shoulder dislocation during a seizure arises not from the seizure itself, but rather from the trauma that occurs when the shoulder contacts the ground upon falling. However, Raptis et al [ 11 ] reported a case of chronic BSASD occurring after a patient experienced seizures without any fall or other traumatic injury. Further information regarding the position of the patient's arms during the seizure and details on any trauma occurring due to the seizure would thus allow valuable insight into the exact mechanism of BSASD resulting from seizure activity.…”
Section: Discussionmentioning
confidence: 99%
“…On review of the literature published in the English language there are eleven previous reports of chronic bilateral anterior glenohumeral dislocation ( Table 2 ). Of these eleven, four were treated non-operatively [ 9 , 10 , 11 , 12 ] and no closed reduction was attempted, four were treated with open reduction alone [ 13 , 14 , 15 , 16 ], two were treated with successful closed reduction and ORIF of the concurrent greater tuberosity fractures [ 17 , 18 ] and one was treated by closed reduction alone [ 19 ].…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%